TIM-1 serves as a receptor for Ebola virus in vivo, enhancing viremia and pathogenesis. - Bethany Brunton; Kai Rogers; Elisabeth K Phillips; Rachel B Brouillette; Ruayda Bouls; Noah S Butler; Wendy Maury (Public Library of Science (PLoS), 2019)
Background T cell immunoglobulin mucin domain-1 (TIM-1) is a phosphatidylserine (PS) receptor, mediating filovirus entry into cells through interactions with PS on virions. TIM-1 expression has been implicated in Ebola virus (EBOV) pathogenesis; however, it remains unclear whether this is due to TIM-1 serving as a filovirus receptor in vivo or, as others have suggested, TIM-1 induces a cytokine storm elicited by T cell/virion interactions. Here, we use a BSL2 model virus that expresses EBOV glycoprotein to demonstrate the importance of TIM-1 as a virus receptor late during in vivo infection. Methodology/principal findings Infectious, GFP-expressing recombinant vesicular stomatitis virus encoding either full length EBOV glycoprotein (EBOV GP/rVSV) or mucin domain deleted EBOV glycoprotein (EBOV GPΔO/rVSV) was used to assess the role of TIM-1 during in vivo infection. GFP-expressing rVSV encoding its native glycoprotein G (G/rVSV) served as a control. TIM-1-sufficient or TIM-1-deficient BALB/c interferon α/β receptor-/- mice were challenged with these viruses. While G/rVSV caused profound morbidity and mortality in both mouse strains, TIM-1-deficient mice had significantly better survival than TIM-1-expressing mice following EBOV GP/rVSV or EBOV GPΔO/rVSV challenge. EBOV GP/rVSV or EBOV GPΔO/rVSV in spleen of infected animals was high and unaffected by expression of TIM-1. However, infectious virus in serum, liver, kidney and adrenal gland was reduced late in infection in the TIM-1-deficient mice, suggesting that virus entry via this receptor contributes to virus load. Consistent with higher virus loads, proinflammatory chemokines trended higher in organs from infected TIM-1-sufficient mice compared to the TIM-1-deficient mice, but proinflammatory cytokines were more modestly affected. To assess the role of T cells in EBOV GP/rVSV pathogenesis, T cells were depleted in TIM-1-sufficient and -deficient mice and the mice were challenged with virus. Depletion of T cells did not alter the pathogenic consequences of virus infection. Conclusions Our studies provide evidence that at late times during EBOV GP/rVSV infection, TIM-1 increased virus load and associated mortality, consistent with an important role of this receptor in virus entry. This work suggests that inhibitors which block TIM-1/virus interaction may serve as effective antivirals, reducing virus load at late times during EBOV infection.